Improved Operating Performance of Mining Machine Picks. (August 2016) - Prokopenko, S; Li, A; Kurzina, I; Sushko, A
Abstract: The reasons of low performance of mining machine picks are stated herein. In order to improve the wear resistance and the cutting ability of picks a new design of a cutting carbide tip insert to be fixed on a removable and rotating pick head is developed. Owing to the new design, the tool ensures a twofold increase in the cutting force maintained longer, a twofold reduction in the specific power consumption of the breaking process, and extended service life of picks and the possibility of their multiple use.